2008
DOI: 10.1186/1472-6920-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Training tomorrow's doctors in diabetes: self-reported confidence levels, practice and perceived training needs of post-graduate trainee doctors in the UK. A multi-centre survey

Abstract: Objective: To assess the confidence, practices and perceived training needs in diabetes care of postgraduate trainee doctors in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…The other limitation of this survey is questionnaire bias. However, our response rates were 60%, which is comparable to other surveys in which trainees or doctors were polled using questionnaires 4 911…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The other limitation of this survey is questionnaire bias. However, our response rates were 60%, which is comparable to other surveys in which trainees or doctors were polled using questionnaires 4 911…”
Section: Discussionsupporting
confidence: 79%
“…The questionnaire in our study is not validated for this purpose. However, the use of self-assessments continues to be used to inform policy makers about deficiencies in postgraduate training8 9 and self-assessment of confidence levels developed by the Royal College of Physicians, UK continues to be used in postgraduate training portfolios. The other limitation of this survey is questionnaire bias.…”
Section: Discussionmentioning
confidence: 99%
“…Among postgraduate trainee doctors in the United Kingdom, only 11% advised patients on lifestyle change for diabetes control 9 . A study among cardiologists, neurologists and other physicians in internal medicine (N=1609) from 232 primary, secondary and tertiary care healthcare institutions in Beijing, China to assess their practices in advising on lifestyle modifications in the management of hypertension 10 found that 48.6% of cardiologists and 28.3% of other physicians prescribe lifestyle modifications to control hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…A study undertaken in the UK in the context of the trend to move long-term management of diabetes from specialist centers to primary care 17 showed that a fifth of the postgraduate trainee doctors would not actively identify the cardiovascular risk factors.…”
Section: Eledrisimentioning
confidence: 99%